1999
DOI: 10.1111/j.1600-0684.1999.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody responses in Africa green monkeys naturally infected with simian immunodeficiency virus (SIVagm)

Abstract: This study assessed the magnitude and cross-reactivity of the neutralizing antibody response generated by natural SIV infection in wild-caught African green monkeys. Neutralizing antibodies of variable potency, sometimes exceeding a titer of 1:1,000, were detected in 20 of 20 SIV-seropositive African green monkeys in Kenya. Detection of those neutralizing antibodies was dependent on the strain of virus and the cells used for assay, where the most sensitive detection was made with SIVagm1532 in Sup T1 cells. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…Humoral immune responses are evident in naturally infected monkeys; however, neutralizing antibody levels are low (2,4,37,73). In naturally infected sooty mangabeys, SIV-specific cytolytic CD8 Ï© T-cell responses are limited, consistent with the observed high levels of SIVsm replication (56; Grant et al, submitted; Silvestri et al, submitted).…”
supporting
confidence: 55%
“…Humoral immune responses are evident in naturally infected monkeys; however, neutralizing antibody levels are low (2,4,37,73). In naturally infected sooty mangabeys, SIV-specific cytolytic CD8 Ï© T-cell responses are limited, consistent with the observed high levels of SIVsm replication (56; Grant et al, submitted; Silvestri et al, submitted).…”
supporting
confidence: 55%
“…It is questionable whether adaptive immune responses contribute to partial viral control and a nonpathogenic course of infection. Since SIV-specific humoral immune responses in chronic infection consist mainly of nonneutralizing envelope-specific antibodies and relatively low titers of Gagspecific antibodies in comparison to AIDS virus-infected humans and Asian nonhuman primates, it is unlikely that humoral immune responses play a major role in the nonpathogenic course of infection (17,25,50). Cellular immune responses have been detected in sooty mangabeys (30).…”
Section: Cd4mentioning
confidence: 99%
“…However, the nonpathogenicity of SIVs in their natural hosts was concluded from the study of only a few host species (African green monkeys [AGMs], sooty mangabeys, and mandrills), and the vast majority of these studies were performed on captive monkeys (12)(13)(14)(15)(16)(17)(18)(19). Over the last 2 decades, these studies consistently reported that the control of disease progression in the natural hosts of SIVs is due neither to control of viral replication nor to SIV-specific adaptive immune responses, as viral loads (VLs) in AGMs, sooty mangabeys, and mandrills are similar to those observed during pathogenic HIV/ SIV infections (12,14,(20)(21)(22)(23) and adaptive immune responses are not quantitatively or qualitatively different from those mounted during pathogenic infections (24)(25)(26)(27)(28)(29)(30). Instead, the lack of disease progression was shown to be the result of adaptation of these natural hosts to control of the deleterious indirect consequences of SIV infection, i.e., excessive levels of immune activation, T cell proliferation, and apoptosis (23,(31)(32)(33).…”
mentioning
confidence: 99%